Fenomena Bentuk dan Dampak Bullying Verbal terhadap Siswa Kelas V di SDN 31 Mataram: Studi Kasus pada Anak Berkebutuhan Khusus - Mauliana Gusfian; Darmiany; Mohammad Archi Maulyda (Mataram University, 2026)
This study aims to analyze the forms of verbal bullying and their impact on students with special needs in grade V of SDN 31 Mataram. Verbal bullying is still a problem in the world of education, but research that focuses on its forms and impacts at the inclusive elementary school level is still limited. This study uses a qualitative descriptive approach with a phenomenological design type involving 3 students with special needs, class teachers, and parents of special needs as research subjects. Data were collected through observation, interviews, and documentation. The results showed that the forms of verbal bullying experienced by students with special needs include teasing, harsh words and imitation of speech. The impacts include emotional impacts such as sadness, fear, and crying; social impacts such as withdrawal from social environments, difficulty adapting to social situations and avoiding interactions with friends; and academic impacts including lack of focus, decreased participation in class and obstacles to learning outcomes. These findings indicate that verbal bullying negatively impacts the emotional, social, and academic development of students with special needs. Therefore, schools and teachers need to strengthen supervision and implement preventive measures to create a safe and inclusive learning environment for all students.